Analysis of the Principles and Elements of Fashion Design Western and Eastern - Angriani, Aidil Dewi (Master Program of Social Science Education of Universitas Negeri Padang, Indonesia, 2026)
This study analyzes the principles and elements that characterize fashion design in Western and Eastern cultures. Clothing initially emerged as a basic human need to protect the body from environmental factors such as sunlight, cold weather, and insect bites. Over time, however, the function of clothing developed beyond protection to include aesthetic, social, and cultural purposes. The way people dress reflects cultural values, social norms, and the level of civilization within a society. As human culture develops, the complexity of thought and creativity also grows, influencing the evolution of fashion design across different historical periods. Fashion design is not only a form of artistic expression but also a representation of cultural identity and social values. Western and Eastern fashion traditions are shaped by different historical, philosophical, and cultural backgrounds, resulting in distinct approaches to design. Western fashion design generally emphasizes individuality, creativity, and structural form, while Eastern fashion design tends to prioritize harmony, symbolism, modesty, and respect for tradition. This study uses a qualitative method with a library research approach by reviewing various books, academic articles, and related literature on fashion design principles. The analysis focuses on design principles such as balance, proportion, rhythm, and unity, as well as design elements including line, color, texture, and form. The results indicate that although both traditions apply similar basic elements, their interpretation differs according to cultural perspectives